Learning outcomes about important Buddhist days by positive reinforcement to cultivate desirable characteristics in being Thai and global citizenship of students Prathom Suksa 1 at Ban Kham Rian School, Tumbon Nhongbua, Phayakkhaphum Phisai District, Mahasarakham Province: - Samrandee , Witsuta; Numnaphol , Kochaporn; Dechomeng , Phattharathida (Asian Journal of Traditional and Innovative Arts and Textiles, 2023)
This research article has the objectivewere 1) To develop learning outcomes about important Buddhist days by positive reinforcement to cultivate desirable characteristics in being thai and global citizenship of students Prathom Suksa 1 at Ban Kham Rian School. 2) To evaluate learning achievement before and after studying the subject important Buddhist days. Thepopulation included students Prathom Suksa 1 at Ban Kham Rian School 22 people, Mahasarakham Primary Education Area Office 2, academic year 2023. Tools usedincluding : learning activity plan, Pre - post test, and Student desirable characteristics assessment form. Statistics include frequency, percentage, mean, and standard deviation. The research results found that: Learning outcomes 22 students, representing 100 percent, was understanding of the desirable characteristics of Thai and global citizenship and able to behave on important Buddhist days and pass the criteria of the development set not less than 70 percentdesired characteristics with progressaarranged in order: Committed to work, Intend to learn, and Discipline. In additional the results of the evaluation of academic achievement of students in Prathom Suksa 1, who took a test about important Buddhist days when receiving teaching and learning by using positive reinforcement activities, it was found that after studying higher than before studying the average score is higher. The average score before studying was 46.00, 46.07 percent, and the average score after studying was 86.70, 86.78 percent.